Dampak Undang-Undang Agraria 1870 terhadap Dinamika Sosial dan Ekonomi Komunitas Arab di Ampel Surabaya, 1870-1930 - Luthfiyah, Widatul; Hannan, Haukil; Syaie, Akhmad Najibul Khairi (Fajar Historia: Jurnal Ilmu Sejarah dan Pendidikan, 2024)
This thesis examines the influence of the Agrarian Law of 1870 on the existence of the Arab community in Ampel, Surabaya, from 1870 to 1930. The issues addressed include the historical emergence of the Agrarian Law, its implementation, and its impact on the socio-economic conditions of the Arab community. This research employs historical methodology through steps of heuristics, verification, interpretation, and historiography, utilizing both historical and sociological approaches. The historical approach narrates events in chronological order, while the sociological approach reveals social processes using social change and economic development theory. The findings indicate that the Agrarian Law of 1870 arose in response to abuses within the Cultivation System and the influence of liberal thought in Europe. Its implementation encompasses regulations regarding Agrarian matters (Agrarische Besluit) and the granting of Erfpacht rights, which established social strata within Surabaya’s society, placing the Arab community of Ampel in the second tier as economic distributors. This article argues that the repercussion of the 1870 Agrarian Law had implications for the economic and social life of the Arab community, while also fostering the emergence of solidarity against foreign cultural impositions, reflected in the establishment of special schools for Arabs and natives.